2010
DOI: 10.1073/pnas.1009492108
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the biophysical characteristics of Plasmodium-falciparum -parasitized red blood cells in microcirculation

Abstract: The pathogenicity of Plasmodium falciparum (Pf) malaria results from the stiffening of red blood cells (RBCs) and its ability to adhere to endothelial cells (cytoadherence). The dynamics of Pf-parasitized RBCs is studied by three-dimensional mesoscopic simulations of flow in cylindrical capillaries in order to predict the flow resistance enhancement at different parasitemia levels. In addition, the adhesive dynamics of Pf-RBCs is explored for various parameters revealing several types of cell dynamics such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
145
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(153 citation statements)
references
References 31 publications
8
145
0
Order By: Relevance
“…In addition, area and volume constraints are imposed to represent the incompressibility of the lipid bilayer and RBC cytosol. The model has been validated in a number of studies, e.g., for the mechanical properties (33,34), as well as rheological and hemodynamic properties of blood flow in healthy (36), malaria-infected (37), and SCA conditions (38). The ISC model is constructed by applying surface tension on a healthy RBC membrane (38), representing the distortion of the cell membrane due to the growth of the intracellular sickle hemoglobin polymers.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, area and volume constraints are imposed to represent the incompressibility of the lipid bilayer and RBC cytosol. The model has been validated in a number of studies, e.g., for the mechanical properties (33,34), as well as rheological and hemodynamic properties of blood flow in healthy (36), malaria-infected (37), and SCA conditions (38). The ISC model is constructed by applying surface tension on a healthy RBC membrane (38), representing the distortion of the cell membrane due to the growth of the intracellular sickle hemoglobin polymers.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11] Thus, central questions regarding the biomechanical factors that control the dynamics, efficiency, and strength of adhesion are still pending. The literature discusses several factors, including receptor and ligand geometry, bond characteristics, cell deformability, and the area of tight contact between the cell and the surface, that might affect the cytoadhesion of parasitized erythrocytes, [12][13][14][15] but their individual or combined contribution has not yet been experimentally specified.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Therefore, the relationship between the hemorheological and hemodynamic properties is of great importance for early diagnosis of such diseases. It is reported that increase in hematocrit 21,22 and aggregation 23 tends to make velocity profile blunt.…”
Section: Introductionmentioning
confidence: 99%